1999
DOI: 10.1063/1.58237
|View full text |Cite
|
Sign up to set email alerts
|

Laser cooling and trapping of neutral atoms

Abstract: The forces felt by atoms when illuminated with resonant radiation can reduce their velocity dispersion and confine them in a region of space for further probing and experimentation. The forces can be dissipative or conservative and allow manipulations of the external degrees of freedom of atoms and small neutral particles. Laser cooling and trapping is now an important tool for many spectroscopic studies. It enhances the density of atoms in phase space by many orders of magnitude reducing the need of large sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A more elaborated model comprises a continuous measurment as a series of instantaneous measurements with the interval between them tending to zero [22]. Nevertheless, this is a controversial issue, but the work in the direction of Paul and Penning traps [21] could be, in a near future, a way to perform this kind of experiments [23].…”
Section: Discussionmentioning
confidence: 99%
“…A more elaborated model comprises a continuous measurment as a series of instantaneous measurements with the interval between them tending to zero [22]. Nevertheless, this is a controversial issue, but the work in the direction of Paul and Penning traps [21] could be, in a near future, a way to perform this kind of experiments [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another important application of radiation pressure is laser cooling. With multiple counter-propagating laser beams, the target particle will receive a force opposite to its direction due to Doppler effect, so that the particle motion is slowed, which means the temperature decreases [13,14]. Further research which combined magnetic field and radiation pressure could cool the atom down to micro or even nano Kal [15].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies address the influence of alcohol on emotional processing using ERP techniques. Orozco and colleagues [122] investigated the role of alcohol on ERP responses to emotional faces. It was found that, following alcohol ingestion male subjects had decreased late positive (P450) amplitudes to male happy faces as compared to placebo.…”
Section: Effects Of Acute Intoxication On Emotion Processing and Perceptionmentioning
confidence: 99%